Free Zones in Libya Between Legislative Reality and Commercial Ambition: A Legal Prospective Study - Mohamed Mouloud Souf (Journal of Scientific and Human Dimensions, 2025)
This research addresses the legal gap surrounding the regulation of free zones in Libya, despite their promising economic and commercial potential. It analyzes the conceptual framework of free zones, examines the current legislative reality in Libya, and highlights the legal and administrative challenges hindering their activation. The study also reviews successful international models of free zone regulation to extract key elements that could inform a future legal vision tailored to the Libyan context.The research concludes that the absence of a dedicated and comprehensive legal framework is one of the main obstacles to the effective implementation of free zones in Libya. It emphasizes the urgent need for a clear legislative structure, supported by an independent regulatory authority and a specialized judicial system. The study offers a set of legal and administrative recommendations aimed at transforming free zones into dynamic tools for trade stimulation and sustainable economic development in Libya.